Experimental test of 4 kW-class Stirling cryocooler for superconducting cable cooling system. (April 2019) - Park, Jiho; Ko, Junseok; Kim, Hyobong; Hong, Yongju; Yeom, Hankil; In, Sehwan; Park, Seongje
Abstract: This research paper focuses on the experimental test of a free-piston Stirling cryocooler driven by a double-acting linear compressor. The cold head of the Stirling cryocooler has been designed and adopted for circulating and sub-cooling liquid nitrogen for the superconducting application, i.e. superconducting cable. The whole system mainly consists of aforementioned Stirling cryocooler and a liquid nitrogen circulation facility including a heater. In this research paper, the experimental validation as a proof of concept has been carried out. During the experiments, temperatures, pressures and several dynamic variables has been acquired as the input conditions. The cooling capacity has been estimated by obtaining thermodynamic properties at the both entrances of the circulator. The relevant operational issues will also be discussed.